The Influence of IT Leadership on Business Continuity: Analysis of the Role of Digital Governance in Increasing Company Competitiveness - Muhammad Fauzan Nur Adillah; Hanif Fakhrurroja (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This research aims to explore and analyze the influence of leadership in Information Technology (IT) on company business continuity with a focus on the role of Digital Governance in increasing competitiveness. Using qualitative literature study methods, this research details the background to the importance of digital transformation in the modern business context, as well as investigating the key role played by IT leadership in guiding organizations towards digital success. The data and research objects involve analysis of texts and scientific literature that includes various sources and frameworks related to IT leadership and Digital Governance. It is hoped that the results of this research will provide a deeper understanding of how effective IT leaders can influence a company's business continuity through the application of Digital Governance principles, which in turn will increase the company's competitiveness in the digital era.